EVOL VING PRINCIPLE OF POLLUTER- PAYS IN ENVIRONMENTAL JURISPRUDENCE (NATIONAL CAPITAL LAW JOURNAL, 2006)
NA
Keywords: Polluter Pays Principle; Environmental Jurisprudence; Sustainable Development; Environmental Protection; Absolute Liability Principle; Precautionary Principle; Environmental Law; National Environment Tribunal; Public Liability Insurance Act